Modulation of immune cells and Th1/Th2 cytokines in insulin-treated type 2 diabetes mellitus - NEKOUA, Magloire Pandoua; AMOUSSOU-GUENOU, KUASSI MARCELLIN (My University, 2017)
Background: The role of the immune system in insulin resistance associated with type 2 diabetes has been suggested. Objectives: We assessed the profile of Th1/Th2 cytokines along with the frequencies of immune cells in insulin-treated type 2 diabetic patients (T2DP). Methods: 45 T2D patients and 43 age-matched healthy subjects were selected. Serum concentrations of T-helper type 1 (Th1) and Th2 cytokines and the frequencies of innate and adaptive immunity cells were assessed. Results: T2DP were hyperglycemic and showed high level of insulin, normal levels of triglycerides and total-cholesterol and without any change in HDL-cholesterol.Compared to healthy subjects, T2DP exhibited significant decreased frequencies of neutrophils, without any change in monocytes, eosinophils and natural killer cells. The percentages of total lymphocytes (CD3+) and CD8+-T-cells decreased whereas those of regulatory T-cells increased without any change in CD4+ T-cells in T2DP. Interestingly, the frequencies of effector CD4+-T and B-cells increased in T2DP. Serum concentrations of IL-2, IFN-γ and IL-4 decreased while IL-10 significantly enhanced in T2DP, suggesting a differentiation of CD4+T helper cells towards IL-10-producing- Teff-cells in these patients. Conclusion: Insulin-treated type 2 diabetes is associated with anti-inflammatory profile consistent with differentiation of CD4+-Th-cells towards IL-10-producing-Teff-cells, concomitant with increased frequencies of Treg and B-cells, and this may probably offer prevention against certain infections or autoimmune/inflammatory diseases.
Keywords: Type 2 diabetes; Insulin; Immune cells; Th1/Th2 polarization